Cutaneous tuberculosis - (:unkn) unknown (TAYLOR & FRANCIS AS, 2000)
Tuberculosis continues to be a significant health problem in developing countries. Although cutaneous tuberculosis is uncommon, disseminating skin involvement may still be seen, especially patients from rural areas. A case is reported of disseminated tuberculosis presenting with different clinical forms of cutaneous lesions, pulmonary and giver involvement in an immunocompetent patient.